Interest Rate and Bank Risk-Taking: The Role of Income Diversity - Shahin, Rana; Khalil, Manal; Sallam, Helmy (International Journal of Accounting and Financial Reporting, 2022)
This research examines the impact of interest rates on the risk-taking appetite of banks in Egypt and how income diversity influences their risk-taking. Furthermore, it contributes to the literature by investigating the association between the interacting effect of interest rate and income diversity shares on bank risk-taking. The sample includes 22 banks operating in Egypt spanning from 2011 to 2020. For the analysis, the cross-sectional time-series generalized least squares regression (GLS) approach is employed. The results reveal that low-interest rates exacerbate bank risk-taking. In addition, larger income diversity restricts the risk-taking behavior of banks. Importantly, the results show that banks with higher levels of income diversity push for less risky positions during the low-interest rate period. Hence, the results provide valuable insights into the importance of the moderating role of income diversity strategies. The results are robust to different proxies of bank risk-taking. The policy implications from this research indicate that bank managers and regulators in Egypt as well as in similar emerging economies shall promote income diversity strategies to ensure the safety and soundness of the banking system at times of low-interest rates.